Quantitative evaluation study of lithium sustainable development policies in China based on the PMC index model - Gao, Jie; Liu, Wei; Xu, Mao; Wang, Bo (Frontiers in Earth Science, 2024)
The sustainable development of lithium is essential for facilitating the low-carbon energy transition and ensuring sustainable economic growth. Understanding the effectiveness of China’s policies on lithium development is vital for advancing these goals. This study constructed a comprehensive policy evaluation system using content analysis and the PMC (Policy Modeling Consistency) index model. A total of 12 representative policies were analyzed, and their performance was visualized through PMC surface diagrams. The evaluation revealed that among the 12 policies, 2 were rated as “excellent,” 9 as “good,” 1 as “acceptable,” and none as “poor.” These results indicate that China’s policies for lithium’s sustainable development are generally well-designed and scientifically grounded. Despite their strengths, the policies exhibit areas for improvement, including low timeliness, insufficient long-term planning, and limited dynamic adjustment mechanisms. Regional policy coordination is also lacking, especially in non-major lithium-producing areas where policy quality tends to be lower. To address these issues, we recommend optimizing future policies by enhancing timeliness and flexibility, improving regional coordination, refining policy tools, and increasing public participation.